EFFECT OF LYKAMIN ON GROWTH AND BIOCHEMICAL COMPOSITION OF LONG WHISKERED CATFISH, MYSTUS GULlO (HAMILTON) FINGERLINGS UNDER LABORATORY CONDITIONS - Rajkumar, M.; Kumaraguruvasagam, K. P.; Maheskumar, K.; Shanmugam, A. (Journal of Indian Fisheries Association, 2015)
A growth trial was conducted to test the effect of Lykamin (dietary supplement) on growth, survival and feed conversion in Mystus gulio. Four isoproteic diets were formulated by incorporating the growth promoter, Lykamin at the levels of 0, 0.25, 0.50 and 0. 75% diet. The crude protein content was 30% in each diet. The diets were fed to triplicate groups of catfish fingerlings twice daily at a level of 5% of the total body weight for 120 days. Regular fortnightly sampling was done to evaluate the growth performance of the experimental animals. Water quality parameters during the experimental period were maintained within the range suitable for catfish. The results showed better specific growth rate, weight gain, protein efficiency ratio and feed conversion ratio in the group which was given 0.75% Lykamin diet. Key words: Lykamin, Mystus gulio, growth, survival, proximate composition